An Array of Dielectric Resonator Antenna for wireless application - Mohd Aras, Mohd Shahrieel; Mohamad Zoinol Abidin, Abd Aziz; Rasin, Zulhani (2008)
This project describes a design on array dielectric resonator antenna using disk shape. The dielectric resonator antenna (DRA) consists of high dielectric constant materials, high quality factors and mounted on a grounded dielectric substrate of lower permittivity. DRA is fabricated from low-loss and high relative dielectric constant material of various shapes whose resonant frequencies are functions of the size, shape and permittivity of the material. Two dielectric resonators is introducing as an array. The selected dielectric disks are operating at frequency of 2.4 GHz with dielectric constant of 34.73. The miscrostrip transmission line has been used as a feeding line for the resonator. The microstrip line is quarter wavelength where the frequency that applied from the input can get same with the output and divider was introduced in this layout. The simulation process was done using Computer Simulation Technology (CST) Microwave Studio. The antenna has been fabricated on the FR-4 microstrip board using the wet etching technique. The DRA is operating at the frequency bands used for IEEE 802.11b/g Wireless LANs.